(untitled) (Research, Society and Development, 2020)
Stored carioca beans usually tend to darken and harden and therefore lose quality and commercial value and are rejected by the consumer. The objective of this study was to evaluate the behavior of four contrasting light tegument genotypes for the aging process (darkening and hardening) for six months. We adopted a mathematical data modeling, based on polynomial regression analyzes of the variables, color and texture, in the different storage conditions, to describe the effects of the treatment and the storage time, in all bean samples and to select the model which best describes the interaction between variables. All genotypes tended to harden, with increasing storage temperature and time, regardless of the degree of browning. The lowest values of hardness, after six months, were verified in both slow and fast darkening beans. The genotype most resistant to darkening was which showed significant hardening over time. In conclusion, the color itself is not the best parameter to be considered to determine the degree of aging of stored beans, which is controlled by complex mechanisms, physicochemical, genetic, biochemical, among others, which in turn are influenced by environmental storage conditions and genotype.